2018
DOI: 10.1161/atvbaha.117.310701
|View full text |Cite
|
Sign up to set email alerts
|

Weibel-Palade Body Localized Syntaxin-3 Modulates Von Willebrand Factor Secretion From Endothelial Cells

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 66 publications
5
34
0
Order By: Relevance
“…A different localization pattern was observed for syntaxin‐3 and CD63, 2 proteins that are normally found both on WPBs and on endosomes . It has previously been shown that CD63 is trafficked to the WPBs via the endosomal system in an annexin A8‐ and AP‐3–dependent manner .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…A different localization pattern was observed for syntaxin‐3 and CD63, 2 proteins that are normally found both on WPBs and on endosomes . It has previously been shown that CD63 is trafficked to the WPBs via the endosomal system in an annexin A8‐ and AP‐3–dependent manner .…”
Section: Resultsmentioning
confidence: 85%
“…EGM-18 was replaced every 2 to 3 days, and after 7 days colonies started to form in some wells. Conditioned media of wells that were >50% confluent were assayed using VWF ELISA 40 to identify candidates no longer secreting VWF. VWF-deficient wells were passaged and expanded for further analysis including immunoblotting of cell lysates and Sanger sequencing and NGS of the genomic DNA isolated with the DNeasy Blood & Tissue kit (Qiagen, Venlo, The Netherlands).…”
Section: Generation Of Crispr-edited Vwf −/− Cbboecsmentioning
confidence: 99%
See 1 more Smart Citation
“…WPBs contain two v‐SNAREs, VAMP3 and VAMP8, of which only VAMP3 has so far been shown to support stimulus‐induced WPB release . t‐SNAREs that take part in WPB release include the SNAP25 homolog SNAP23, syntaxin‐3, syntaxin‐4, and most likely also syntaxin‐2 . Owing to their promiscuous nature, various combinations of these SNAREs exist: in endothelial cells, syntaxin‐4 engages with SNAP23 and VAMP3 or VAMP8 , and syntaxin‐3 primarily interacts with VAMP8 and SNAP23 .…”
Section: Exocytotic Machinery Of Wpbsmentioning
confidence: 99%
“…This suggests that endothelial cells can employ at least three (syntaxin‐4–SNAP23–VAMP3, syntaxin‐4–SNAP23–VAMP8, and syntaxin‐3–SNAP23–VAMP8) and possibly more distinct SNARE complexes for release of WPBs. Interestingly, whereas syntaxin‐4 is localized on the plasma membrane, syntaxin‐3 is found on WPBs , suggesting that, in certain cases, WPBs can also function as the acceptor compartment during fusion.…”
Section: Exocytotic Machinery Of Wpbsmentioning
confidence: 99%